Manajemen Dakwah, Penyiaran Islam, Dan Tantangannya Di Era Globalisasi - Mustofa Ibrahim; Syahril Fathulloh; Taj Sab’a Samawat; Meity Suryandari (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
Advances in technology and information, making the way of preaching is also experiencing developments. Da'wah is no longer carried out in a simple way, but begins to take advantage of advances in information technology so that the message of da'wah is more widespread and can be carried out effectively. Da'wah activities are mass in nature, so the recipients of da'wah messages are not only in certain circles. Da'wah can use media that are used as communication media, such as newspapers, radio, television, alternative media and so on. The existence of the media is very influential on the content of da'wah delivered to the community. The media can form opinions and even change people's behavior. Along with that, the presence of the media brings positive as well as negative values. The challenges of da'wah media in the era of globalization are in various forms, so far people are familiar with da'wah both traditionally and in the media. Islamic broadcasting here is all forms of broadcasting delivered with the aim of broadcasting Islamic religious teachings to the public so that they understand and practice them for the sake of happiness in this world and in the hereafter